2009
DOI: 10.1177/1084822309348693
|View full text |Cite
|
Sign up to set email alerts
|

Lifting the Home Care Veil From Depression: OASIS-C and Evidence-Based Practice

Abstract: There is a high prevalence of depression among the general elderly population. There is an even higher prevalence among elderly receiving home health care, with a conservative estimate of 13.5% having clinically defined major depression. The Medicare Home Health Benefit provides limited coverage, eligibility, and payment for mental health services, and the national Outcome Assessment and Information Set (OASIS) assessment instrument has had limited requirements on assessing, diagnosing, and treating depression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…Nevertheless, HHC agencies have been slow to acknowledge the full potential of the nurse-patient relationship with depressed geriatric HHC patients (Markle-Reid et al, 2011;Suter et al, 2008). Notably, HHC nurses are not currently recognized for the important therapeutic work they perform, which can be crucial or additive to depression care management, and it is also not reimbursed by the Medicare prospective payment system (PPS; Cabin, 2010). Moreover, relatively little is known about which therapeutic strategies can most effectively treat older HHC patients with depressive symptoms and concomitant disability (Forsman, Schierenbeck, & Wahlbeck, 2011).…”
Section: Depression Management and Hhc Nursingmentioning
confidence: 99%
“…Nevertheless, HHC agencies have been slow to acknowledge the full potential of the nurse-patient relationship with depressed geriatric HHC patients (Markle-Reid et al, 2011;Suter et al, 2008). Notably, HHC nurses are not currently recognized for the important therapeutic work they perform, which can be crucial or additive to depression care management, and it is also not reimbursed by the Medicare prospective payment system (PPS; Cabin, 2010). Moreover, relatively little is known about which therapeutic strategies can most effectively treat older HHC patients with depressive symptoms and concomitant disability (Forsman, Schierenbeck, & Wahlbeck, 2011).…”
Section: Depression Management and Hhc Nursingmentioning
confidence: 99%
“…Today, in-home counseling services are provided by mental health professionals from various backgrounds to treat a wide array of presenting problems, including both mood and psychotic disorders (Kalucy et al, 2003), antisocial behavior (Curtis, Ronan, & Borduin, 2004), substance abuse (Gruber & Fleetwood, 2004), and diabetes (Harris & Mertlich, 2003). While clients most commonly treated are children and adolescents who possess emotional and behavioral disturbances (Liddle et al, 2005;Mattek et al, 2010, Mosier et al, 2001, in-home counseling has also been shown to be a promising treatment with families (Curtis, Ronan, & Borduin, 2004;Liddle et al, 2005;Yorgason et al, 2005) and older persons (Cabin, 2010;Maxfield & Segal, 2008). Typically, the population of clients who receive in-home counseling are referred to as multichallenged or multistressedfamilies, and possess multiple problems that are chronic and severe in nature (Adams & Maynard, 2000;Lawick & Bom, 2008;).…”
Section: Introductionmentioning
confidence: 99%
“…A training packet on late-life depression screening and interventions was developed specifically for this study by the research team based on national nursing practice depression assessment guidelines, evidence-based assessment procedures, and non-pharmacological and pharmacological intervention protocols used effectively in other studies to facilitate the trainers' education programs within their agencies and provide a standardized curriculum. 5,18,19,[58][59][60] Table 1 presents an outline of the objectives and educational content of the TTT.…”
Section: Depression Screening and Intervention Training Programmentioning
confidence: 99%